Dispersal of Philippine eagles released in the forests of Mindanao, Philippines - Abaño, Tatiana Rose C. (Institute of Biology, College of Science, University of the Philippines Diliman, 2012)
From 2004-2011, seven individuals of the critically endangered Philippine Eagle Pithecophaga jefferyi had been released in the forests of Mindanao, Philippines. This study is the first attempt to analyze the results of experimental releases of three captive-bred and our rehabilitated Philippine Eagles. During this period, one Philippine Eagle (Kabayan) was released in Mount Apo Natural Park; another five eagles (Kagsabua, Tinuy-an, Hineleban, Kalabugao and Chick 23) were released in Mount Kitanglad Range Natural Park while another eagle (Hagpa) was released in Mount Kimangkil. The dispersal pattern of the eagles during the first few months of their release were described through data obtained from satellite telemetry. The possible factors behind their dispersal patterns were further determined through radio telemetry and direct observation. Based on the results of this study, recommendations are provided to improve future release protocols.